Empathy and perception of animal welfare among Mexican students of professions related to the use, handling and care of animals - Torres Cardona, María Guadalupe (2022)
The aim of this study was to know the level of human-animal and human-human empathy and the perception of animal welfare in students of professions related to the use, handling and animal care of Mexican institutions of higher education. An electronic questionnaire (Google Forms) was applied where the Paul Empathy Scale (22 items) was included items to measure the level of human-animal empathy; the Interpersonal Reactivity Index (27 items) to measure human-human empathy and the questionnaire to measure attitudes towards animal abuse as an indicator of perception of animal welfare (14 items). In total, 1688 surveys were answered from 35 institutions. The results show that women had significantly higher scores than male students in human-animal, human-human empathy and perception of animal well-being. There was a reduction in human-animal empathy from the second year of university education in men and from the third year in women. Students with a preference towards animal production showed lower values of human-animal empathy and perception of animal welfare. The introduction of content in the curricula is considered necessary to develop empathy skills towards animals from the beginning and throughout the professional training.